Uncommon presentation of a patient with hereditary haemorrhagic telangiectasia - I. N. Walmsley; V. Ratnamalala; J. Indrakumar (Sri Lanka College of Internal Medicine, 2024)
Hereditary hemorrhagic telangiectasia (HHT) is an autosomal dominant disorder. It is clinically characterised by telangiectasia, recurrent epistaxis, and visceral vascular lesions. We report a case of HHT without a significant family history. A 16-year-old girl presented with multiple episodes of bleeding, including uncommon sites, over a period of ten months. She denied a family history of bleeding. Her clinical examination was unremarkable. Investigations including basic and second-line coagulation tests were normal. Subsequently multiple telangiectasias in the right nasal septum and capillary dilatation in the bladder wall were detected. According to Curaçao diagnostic criteria, a diagnosis of HHT was made. As her bleeding was self-limiting, follow up was arranged to monitor complications.